2014
DOI: 10.1021/ac502677n
|View full text |Cite
|
Sign up to set email alerts
|

Camera-Based Ratiometric Fluorescence Transduction of Nucleic Acid Hybridization with Reagentless Signal Amplification on a Paper-Based Platform Using Immobilized Quantum Dots as Donors

Abstract: Paper-based diagnostic assays are gaining increasing popularity for their potential application in resource-limited settings and for point-of-care screening. Achievement of high sensitivity with precision and accuracy can be challenging when using paper substrates. Herein, we implement the red-green-blue color palette of a digital camera for quantitative ratiometric transduction of nucleic acid hybridization on a paper-based platform using immobilized quantum dots (QDs) as donors in fluorescence resonance ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 50 publications
2
85
0
Order By: Relevance
“…Noor and Krull reported on a DNA diagnostic platform ( Figure 14) using a paper-based fluorescence resonance energy transfer (FRET) sensor and an iPhone or iPad for fluorescence detection [85]. …”
Section: Sensing Of Dnamentioning
confidence: 99%
“…Noor and Krull reported on a DNA diagnostic platform ( Figure 14) using a paper-based fluorescence resonance energy transfer (FRET) sensor and an iPhone or iPad for fluorescence detection [85]. …”
Section: Sensing Of Dnamentioning
confidence: 99%
“…Salt aging is used to increase the loading capacity of oligonucleotide probes to the surface of QDs by screening the electrostatic repulsion associated with the negative charge of the sugar-phosphate backbone of oligonucleotides [21]. We have previously reported that without the salt-aging step, an average of 17 oligonucleotide probes can be self-assembled to the surface of similar GSH-QDs when incubated with 40 times molar excess of the oligonucleotide probes [21]. However, with the salt-aging step, an average of 35-40 oligonucleotide probes can be self-assembled to the surface of the GSH-QDs for the aforementioned preparation [21].…”
Section: Notementioning
confidence: 99%
“…We have previously reported that without the salt-aging step, an average of 17 oligonucleotide probes can be self-assembled to the surface of similar GSH-QDs when incubated with 40 times molar excess of the oligonucleotide probes [21]. However, with the salt-aging step, an average of 35-40 oligonucleotide probes can be self-assembled to the surface of the GSH-QDs for the aforementioned preparation [21].…”
Section: Notementioning
confidence: 99%
See 1 more Smart Citation
“…The state of the art personal healthcare industry has put significant emphasis on the development of easy to use portable diagnostic platforms like Integrated quantum dot barcode smartphone optical device for wireless multiplexed diagnosis [17], camera-based ratio metric fluorescence transduction on a paper-based platform using immobilized quantum dots as FRET donors [18]. Algar et al, showed QDs as simultaneous acceptors and donors in time gated FRET relay events and their application in biosensing [19].…”
Section: Quantum Dotsmentioning
confidence: 99%